Peranan Kelompok Bimbingan Ibadah Haji ( KBIH) Dalam Mencetak Kemandirian Jamaah Calon Haji - Abd Wahid (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2019)
The Hajj Guidance Group (KBIH) was established with the aim of accompanying jama'ah in carrying out the pilgrimage to the mabrur pilgrimage. In carrying out the guidance of the Hajj on KBIH, it is of course necessary to apply good management functions, so that the guidance process can run well and effectively according to the desired program, so that the presence of KBIH is able to deliver and print quality and independent pilgrims. The government through the ministry of religion provides space for the community to hold pilgrimage guidance. In this context the existence and role of KBIH is very strategic, so it needs good preparation in its implementation. The role and function of KBIH in organizing the Hajj is to prepare pilgrims through manasik guidance so that Jama'ah can be independently knowledgeable in carrying out the Hajj in the holy land. KBIH volunteered to prepare the pilgrims to carry out a series of Hajj rituals independently according to the Shari'ah so that they could achieve the goals desired by each congregation, namely the title of Mabrur Hajj.